Two New Species of Ctenoblepharis (Reptilia, Iguanidae) from the Arid Environments of the Central Argentina (Mendoza Province) - Cei, José Miguel Alfredo María (1974)
Two new species of the iguanid genus Ctenoblepharis, C. donoso barrosi and C. rabinoi, are described, on the basis of adult specimens collected from the arid lands of the southeastern Mendoza province, Argentina. General notes on the geographical distribution and ecological features of the genus are included.